2020
DOI: 10.5194/gmd-2020-175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of the PALM model system 6.0 in real urban environment; case study of Prague-Dejvice, Czech Republic

Abstract: Abstract. The PALM 6.0 model system has been rapidly developed in the recent years with respect to its capability to simulate physical processes within urban environments. In this regard, it includes e.g. energy-balance solvers for building and land surfaces, a radiative transfer model to account for multiple reflections and shading, as well as a plant-canopy model to consider the effects of plants on the (thermo)dynamics of the flow. This study provides a thorough evaluation of modelled meteorological, air ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…In this study, the sensitivity of air and surface temperature, MRT, PET and PM10 within the PALM6.0 as a response to modification of basic surface material parameters as well as to common urbanistic strategies was evaluated. It was found that for this kind of simulations, the albedo and emissivity as well as thermal conductivity of walls and volumetric heat capacity of the materials play an important role (Belda et al, 2020). Figure 16.…”
Section: Example For a Real-world Applicationmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, the sensitivity of air and surface temperature, MRT, PET and PM10 within the PALM6.0 as a response to modification of basic surface material parameters as well as to common urbanistic strategies was evaluated. It was found that for this kind of simulations, the albedo and emissivity as well as thermal conductivity of walls and volumetric heat capacity of the materials play an important role (Belda et al, 2020). Figure 16.…”
Section: Example For a Real-world Applicationmentioning
confidence: 94%
“…Furthermore, a thorough validation of PALM in a real urban environment against in situ measurements is presented in Resler et al (2020). They especially focus on the representation of surface temperatures in PALM at different types of urban surfaces and also emphasize the need for accurate input data to be in agreement with in situ measurements.…”
Section: Example For a Real-world Applicationmentioning
confidence: 99%
“…The simulations presented herein were performed for a domain in Prague-Dejvice, Czech Republic. At outset, they were validated against a study by [15].…”
Section: Introductionmentioning
confidence: 99%
“…The model source code version 6.0 in revision r4508 used in this article is also available from https://doi.org/10.25835/0073713 (Resler et al, 2020a). The configurations and inputs of the model for all simulated episodes are available from http://hdl.handle.net/11104/0315416 (Resler et al, 2020b).…”
Section: Lessons Learnt and Outlook For Future Improvementsmentioning
confidence: 99%